2019
DOI: 10.1108/ijchm-07-2018-0592
|View full text |Cite
|
Sign up to set email alerts
|

When and why does relative leader-member exchange enhance service performance?

Abstract: Purpose This paper aims to examine the mediating roles of self-efficacy and team commitment in linking service employees’ relative leader-member exchange (RLMX) with customer service behaviors and also the moderating roles of team-level differentiations in leader-member exchange (LMX) and team-member exchange (TMX) in influencing these mediation processes. Design/methodology/approach Data were collected from 467 customer-contact employees working in hotel restaurants. Hierarchical linear modeling analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…More importantly, personal control often serves as a buffer against stressors or negative life events, and thus, the research has shown that individuals with higher levels of personal control have fewer health problems and higher levels of wellbeing when encountering a crisis (Greenaway et al, 2015). Further still, ample studies have demonstrated similar results in the hospitality workplace (Wang et al, 2020;Xu et al, 2020;Yoon and Yoon, 2019).…”
Section: Linking Stressors To Well-being and Career Change Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, personal control often serves as a buffer against stressors or negative life events, and thus, the research has shown that individuals with higher levels of personal control have fewer health problems and higher levels of wellbeing when encountering a crisis (Greenaway et al, 2015). Further still, ample studies have demonstrated similar results in the hospitality workplace (Wang et al, 2020;Xu et al, 2020;Yoon and Yoon, 2019).…”
Section: Linking Stressors To Well-being and Career Change Intentionmentioning
confidence: 99%
“…Finally, this study examined the mediating role of personal control in the proposed model and further operationalized the psychological sense of personal control as self-efficacy. Several similar concepts, such as self-esteem or psychological capital, have frequently been used to examine the individual differences when coping with stressful working environments in hospitality (Wang et al, 2020;Xu et al, 2020;Yoon and Yoon, 2019) or adverse life events (Price et al, 2002;Romppel et al, 2013). The study results showed that possessing high personal control qualities can help buffer adverse outcomes, which is consistent with previous studies.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…This helps them gain positive feedback from others and thus maintain their level of self-esteem (Wang et al, 2020), which may make them less motivated to engage in behaviors that will harm interpersonal harmony. LMX helps in the maintenance of one's self-image by providing support and resources (Yoon and Yoon, 2019), consequently mitigating the relationship between daily self-esteem and daily interpersonal harmony. Therefore, the influence of low LMX may be stronger than that of high LMX on the relationship between daily self-esteem and daily interpersonal harmony.…”
Section: Influence Of Daily Self-esteem On Daily Interpersonal Harmonymentioning
confidence: 99%
“…The importance of social network ties increases CCS not only directly (H7, β 5 0.323, p 5 0.014), but also indirectly via its significant effect on openness to change (H6, β 5 0.247, p 5 0.040). In this context, we see a strong relationship with the discussion about team commitment and its mediating effect between leader-membership exchange and customer service, which has lately been published by Yoon and Yoon (2019).…”
Section: Implications For Researchmentioning
confidence: 84%
“…In this context, Cheung and To (2010) state that employees' involvement plays an important mediating role between the management commitment to service quality and its organizational output in terms of customer perception of service performance. Also, He et al (2001) find that service climate improves customer satisfaction, which is mediated by employee commitment (see also Garg and Dhar, 2016;Jauhari et al, 2017), and Yoon and Yoon (2019) focus on team commitment and self-efficacy in the context of enhancing service performance. Finally, Lau et al (2017) argue that the ethical work climate significantly enhances the employees' affective commitment and proactive customer service performance.…”
Section: Influence Of Informal Institutions On Ccsmentioning
confidence: 98%